An Excellent Clinical and Radiological Response Pattern to Pembrolizumab in a Patient With Metastatic Adrenocortical Carcinoma and Lynch Syndrome - Yuki Shimozawa; Yosuke Yasuda; Emiko Sugawara; Ryosuke Oki; Kosuke Takemura; Tetsuya Urasaki; Ryo Fujiwara; Noboru Numao; Junji Yonese; Takeshi Yuasa (IJU Case Reports)
ABSTRACT Introduction The prognosis of unresectable metastatic adrenocortical carcinoma is very poor. We report a case of Lynch syndrome accompanying metastatic adrenocortical carcinoma treated with pembrolizumab. Case Presentation A 73‐year‐old woman was diagnosed with left adrenocortical carcinoma and multiple lung, liver, and lymph node metastases. First‐line mitotane therapy failed due to toxicity and progressive disease. Immunohistochemical analysis of mismatch repair proteins revealed an MSH6 deficiency. Pembrolizumab monotherapy was started for microsatellite instability‐high/mismatch repair–deficient malignant disease. After the first administration, we experienced temporal clinical findings considered to reflect the collapse of tumors. She gained remarkable reductions in all lesions after four cycles. Genetic analysis disclosed the germline pathogenic variant of MSH6, so this case was diagnosed as Lynch syndrome. Conclusion We report a patient with metastatic adrenocortical carcinoma in Lynch syndrome who demonstrated an excellent response to pembrolizumab. Genetic analyses can play a beneficial role in cases of adrenocortical carcinoma.